Makna Keluarga pada Kelompok Mafia: Analisis Semiotika Dalam Film The Godfather-I (Jurnal Kajian Media, 2017)
The family is a small group of people where a human being starts learning to socialize with other human beings, in families there are levels ranging from grandparents, fathers, to grandchildren. All humans in this world need a family and must have family since birth, not least Italian mafia. The Italian Mafia is an organization based on kinship and the head of the family in the mafia as well as the head of the organization. Italy has a great variety of cultures, especially about families, in the Italian family culture is something that should take precedence over anything else. Talking about the mafia is certainly a lot of movies that make stories based on the story of the mafia, one of which is the movie The Godfather by Francis Ford Coppola which is lifted from the novel by Mario Puzo. In the 1970s this film includes a film that topped the box office in the world until defeated by The Shawsank Redemption. We can see how the mafia treats the family and how the family system in the mafia has been the question of many people, the most important is how we can know the meaning of families in the Italian mafia through this article. This research uses descriptive qualitative research method with semiotic approach according to John Fiske, the researcher will analyze scene per scene in The Godfather movie to know how the meaning of family in Italian mafia. Keywords: Meaning. Family. Mafia. Semiotics. The Godfather I.